2013
DOI: 10.1080/10538712.2013.735357
|View full text |Cite
|
Sign up to set email alerts
|

Maltreatment and Depression in Adolescent Sexual Offenders with an Autism Spectrum Disorder

Abstract: This study examined the self-reported presence and severity of abuse, neglect, and depressive symptoms for 43 adolescents adjudicated delinquent due to a sexual offense. Twenty-seven of the adolescent sexual offenders were also diagnosed with an autism spectrum disorder, and 16 did not carry an autism spectrum disorder diagnosis. Both groups reported moderate to high levels of abuse and neglect. Adolescent sexual offenders with an autism spectrum disorder reported significantly higher depressive symptoms than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 35 publications
1
19
0
3
Order By: Relevance
“…In the group of adolescents with an ASD, depressive symptoms were more likely to be found in those who reported severe levels of emotional abuse and/or emotional neglect. The findings of Bleil Walters and colleagues is consistent with the theory outlined by Sobsey and Mansell's (1997) which stated that in relation to emotional abuse and/or emotional neglect children with ASD may, as a result of their impaired social knowledge and problem-solving abilities, be more likely to experiences difficulties in coping with verbal assaults and demeaning statements made by adults (Bleil Walters, Hughes, Sutton, Marshall, Crothers, Lehman et al, 2013).…”
Section: R V Thompson (2012)supporting
confidence: 79%
See 1 more Smart Citation
“…In the group of adolescents with an ASD, depressive symptoms were more likely to be found in those who reported severe levels of emotional abuse and/or emotional neglect. The findings of Bleil Walters and colleagues is consistent with the theory outlined by Sobsey and Mansell's (1997) which stated that in relation to emotional abuse and/or emotional neglect children with ASD may, as a result of their impaired social knowledge and problem-solving abilities, be more likely to experiences difficulties in coping with verbal assaults and demeaning statements made by adults (Bleil Walters, Hughes, Sutton, Marshall, Crothers, Lehman et al, 2013).…”
Section: R V Thompson (2012)supporting
confidence: 79%
“…Lastly, a recent systematic review investigated the literature which explored sexual offending in individuals with ASD (Allely & Creaby-Attwood, 2016). The review highlighted that there were only a few case reports (N = 7) on sexual offending in individuals with ASD ( (Brendel, Bodkin, Hauptman, & Ornstein, 2002;Milton, Duggan, Latham, & Tantam, 2002;Murrie, Warren, Kistiansson, & Dietz, 2002;Ray, Marks, & Bray-Garretson, 2004;Haskins & Silva, 2006;Griffin-Shelley, 2010;Chan & Saluja, 2011) and only a small number of prevalence studies (N = 7) were identified (Mouridsen, Rich, Isager, & Nedergaard, 2008;Långström, Grann, Ruchkin, Sjöstedt, & Fazel, 2008;'t Hart-Kerkhoffs, Jansen, Doreleijers, Vermeiren, Minderaa, & Hartman, 2009;Kumagami & Matsuura, 2009;Bleil Walters et al, 2013;Søndenaa, Helverschou, Steindal, Rasmussen, Nilson, & Nøttestad, 2014). Some of the case studies identified in the review by Allely and Creaby-Attwood (2016) clearly highlight the need to consider these innate vulnerabilities which may increase the risk of an individual with ASD being charged with a sexual offence.…”
Section: Risk Factors For Inappropriate Sexual Behaviour or Sexual Ofmentioning
confidence: 99%
“…Only a small group of adults with ASD reported feelings of asexuality (Gilmour et al 2012). A number of studies and case reports describe sexual problems (e.g., offensive behaviours) and specific sexual behaviours (e.g., paraphilias) in people with ASD ( Baron-Cohen 1988;Bleil Walters et al 2013;Chan and Saluja 2011;Cooper et al 1993;Griffin-Shelley 2010;Hellemans et al 2007;Kohn et al 1998;Milton et al 2002;Murrie et al 2002;Ray et al 2004;Silva et al 2002). It remains undetermined, however, whether there is a higher prevalence of problematic behaviour and negative sexual experiences in people with ASD compared to the general population.…”
Section: Research On Sexuality and Asdmentioning
confidence: 99%
“…This type of study could help determine which independent variable has the largest, or smallest, impact on the dependent variable. Literature has been consistent in connecting a history of trauma and neglect with higher rates of depression and anxiety in juveniles with sexual behavior problems [17,[55][56][57][58][59].…”
Section: Recommendationsmentioning
confidence: 92%